PENGUATAN PEMASARAN DIGITAL UMKM PRO FARM MELALUI SOSIALISASI, PELATIHAN, DAN MARKETPLACE ONLINE - Tatik Amani; Ahmad Iskandar Rahmansyah; Aries Budi Widayanto; Siti Masluha (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Pro Farm, a producer of goat-manure organic fertilizer in Dringu, Probolinggo, faces marketing constraints due to reliance on offline sales and local promotions. This community program aims to strengthen competitiveness through a simple, measurable, capacity-fit digital marketing rollout. The intervention comprised three stages: (1) socialization to align understanding, select priority channels (Instagram, Shopee, Tokopedia, Lazada), and set performance indicators; (2) training on promotional content and account management—product photography, short video, copywriting, scheduling, and responsive service; and (3) assisted setup of social media and online stores, including storefront curation, product descriptions, reply templates, and daily operating procedures. Results indicate improved organizational readiness: objectives, posting cadence, content pillars, and style standards were agreed; an active Instagram account and marketplace shops present clear information with consistent calls to action; the service flow from comments to chat to checkout was shortened; and weekly metric tracking began (follower growth, reach, storefront visits, chat–order ratio, review quality). Findings emphasize that digital adoption depends less on budget and more on consistent execution, continuous learning, and role governance. Recommended next steps include strengthening social proof, optimizing keywords, testing content variants, fostering local collaborations, and securing accounts via two-factor authentication and access management. The three-stage model is replicable for agribusiness MSMEs with local adaptations, enabling market expansion, revenue growth, and business sustainability, grounded in field data and customer needs.